Preclinical Absorption, Distribution, Metabolism, and Excretion of Sodium Danshensu, One of the Main Water-Soluble Ingredients in Salvia miltiorrhiza, in Rats - Meng, Xiangguo; Jiang, Jingjing; Pan, Hui; Wu, Shengyuan; Wang, Shuowen; Lou, Yuefen; Fan, Guorong (Frontiers in Pharmacology, 2019)
In this study, the absorption, distribution, metabolism and excretion (ADME) of sodium danshensu (sodium D/L-(+)-β-(3, 4-dihydroxyphenyl) lactate), one of the main water-soluble active constituents in Salvia Miltiorrhiza, were evaluated in rats. Pharmacokinetic study was evaluated in doses of 15, 30 and 60 mg/kg after intravenous administration of sodium danshensu. Bioavailability study was evaluated by comparing between 30 mg/kg (I.V.) and 180 mg/kg (P.O.) of sodium danshensu. Tissue distribution, metabolism and excretion were evaluated at 30 mg/kg (I.V.) of sodium danshensu. Following intravenous administration, sodium danshensu exhibited linear pharmacokinetics in the dose range of 15-60 mg/kg. Sodium danshensu appeared to be poorly absorbed after oral administration, with an absolute bioavailability of 13.72%. The primary distribution tissue was kidney, but it was also distributed to lung, stomach, muscle, uterus, heart, etc. Within 96 h after intravenous administration, 46.99% was excreted via urine and 1.16% was excreted via feces as the parent drug. Biliary excretion of sodium danshensu was about 0.83% for 24 h. Metabolites in urine were identified as methylation, sulfation, both methylation and sulfation, and acetylation of danshensu. Sodium danshensu can be developed as an injection because of its poor oral bioavailability. In conclusion, sodium danshensu is widely distributed, mainly phase II metabolized and excreted primarily in urine as an unchanged drug in rats.